A novel stability-indicating method for determination of a new antidepressant effect of vortioxetine in a pharmaceutical formulation by using RP-HPLC - Gizem Tiris; Cansu Alver; Nevin Erk (SpringerOpen, 2020)
Abstract Background A novel rapid, accurate, and stability-indicating reversed-phase high performance liquid chromatographic (RP-HPLC) and first derivative spectrophotometric determination were explained for the assay of vortioxetine (VRT) in bulk and pharmaceutical formulations. For RP-HPLC method, optimal separation and determination of VRT were achieved with a Waters Symmetry C18, (100 × 4.6 mm, 3.5 μm) analytical column using a mobile phase consisting of methanol:0.05 M potassium dihydrogen phosphate (pH:3.0 ± 0.05) (30:70, v/v) in isocratic mode with flow rate of 1.3 mL min−1. Injection volume was 20 μL. The maximum absorption wavelength of VRT is 225.0 nm; hence, 225.0 nm was studied as the detection wavelength and column at 50 °C temperature. The caffeine was used as the internal standard (IS). On the other hand, the first derivative spectrophotometric method for the analysis of vortioxetine was performed by measuring the amplitude at 251.7 and 272.6 nm. Result The HPLC method was found to be linear in the concentration ranges of 10.0-70.0 μg mL−1 with the coefficient value R 2 of 0.9998, and the mean recovery value was 100.7%. Further stability studies were done through exposure of the analyte solutions to various stress conditions: acid, alkali hydrolysis, chemical oxidation, and exposure to UV radiation. For the first derivative spectrophotometric method, linearity was observed in the concentration range 6.0-30.0 μg mL−1 (for 237.7 nm R 2 = 0.9999 and for 257.2 nm R 2 = 0.9997). Conclusion The methods were validated in accordance with ICH guidelines with respect to linearity, accuracy, specificity, limit of detection, precision, and limit of quantification.